Parasites and genetic diversity in an invasive bumblebee - Jones, Catherine M (J Anim Ecol, 2014)
1. Biological invasions are facilitated by the global transportation of species and climate change. Given that invasions may cause ecological and economic damage and pose a major threat to biodiversity, understanding the mechanisms behind invasion success is essential. 2. Both the release of non-native populations from natural enemies, such as parasites, and the genetic diversity of these populations may play key roles in their invasion success. 3. We investigated the roles of parasite communities, through enemy release and parasite acquisition, and genetic diversity in the invasion success of the non-native bumblebee, Bombus hypnorum, in the United Kingdom. 4. The invasive B. hypnorum had higher parasite prevalence than most, or all native congeners for two high-impact parasites, probably due to higher susceptibility and parasite acquisition. Consequently parasites had a higher impact on B. hypnorum queens’ survival and colony-founding success than on native species. Bombus hypnorum also had lower functional genetic diversity at the sex-determining locus than native species. Higher parasite prevalence and lower genetic diversity have not prevented the rapid invasion of the United Kingdom by B. hypnorum. These data may inform our understanding of similar invasions by commercial bumblebees around the world. 5. This study suggests that concerns about parasite impacts on the small founding populations common to re-introduction and translocation programs may be less important than currently believed.